Different roles of resilience in a non clinical sample evaluated for family stress and psychiatric symptoms. (October 2016) - Collazzoni, Alberto; Stratta, Paolo; Tosone, Adele; Rossetti, Maria Cristina; D'Onofrio, Simona; Rossi, Alessandro
Abstract: The aim of this study is to investigate the relationship between resilience, risky family and psychiatric symptoms in order to understand which role resilience may have. 608 post-doc course students (323 males and 285 females) were recruited and evaluated through the Resilience Scale for Adult, the Risky Family Questionnaire and the Brief Symptom Inventory. A cluster analysis was implemented to understand the possible associations among the variables, showing four clusters; then a correlation analysis for each cluster was carried out. There was a significant and meaningful correlation pattern for cluster 1. Subsequently a Sobel test in cluster 1 was implemented, with a significant mediating role for resilience. Resilience is associated with less symptoms in Clusters 1 and 2, but in different ways. It has a protective role, mediating the relation between risky family and psychiatric symptoms in Cluster 1. Meanwhile it has a compensatory effect buffering the symptoms in Cluster 2. Clusters 3 and 4 show a high level of family stress and symptoms but a low level of resilience. It is possible to hypothesize that resilience does not "work" when there has been a high past risky family and so resilience could not have protective or compensatory effect. Highlights: Resilience is a positive factor promoting wellbeing buffering from stress; Risky family is a favoring factor for psychiatric symptoms in adult age; Low psychiatric symptoms pass through resilience protective/compensatory pathways; A high level of negative past family stress may interfere with resilience growth.